Avoiding Social Discord via Islamic Religious Education Rooted in Multiculturalism Islamic Religious Education - Hasra, Ratni; Arief Sah, Moh.; Mashuri, Saefudin; Ubadah, Ubadah (Universitas Al-Amien Prenduan, 2025)
This study examines the methods used by Islamic Religious Education teachers to instill multicultural values aimed at preventing social conflict among students at SMA Negeri 1 Sigi. Johan Galtung’s conflict resolution theory and Albert Bandura’s social learning theory act as essential analytical frameworks to comprehend social conflict dynamics and the strategic role of IRE teachers. The study employs a qualitative case study method, gathering data via observation, interviews, and documentation. Data analysis employs the interactive model proposed by Miles and Huberman, with validity assured via triangulation of sources, theories, and methods. The results indicate that Islamic education based on multicultural principles and local knowledge can act as an effective tool not only for avoiding social discord but also for promoting a culture of harmony in a diverse society. This includes thoughtful discussions, incorporating religious values into social settings, fostering a fair educational atmosphere, engaging in interfaith and intercultural initiatives to improve positive interactions among groups, collaborative artistic endeavors that convert conflict into collective creativity, role-playing exercises that prepare individuals for peaceful reactions through practice, enhancing critical thinking and empathy, and demonstrating tolerance along with conflict resolution techniques. Educators engage not just in resolving conflicts (peace-making) but also in promoting a lasting culture of tolerance (peace-building) and ensuring order via inclusive regulations (peace-keeping), serving as role models and supporting inclusive settings (reciprocal determinism). This study provides a model for merging Pancasila values with Islamic education on a national scale and supplies a structure for teaching methods that harmonize religious.